Detection and Classification of Power Quality Disturbances Using LSTM - Fatma Zohra Dekhandji; Abdelmadjid Recioui; Athmane Ladada; Taha Slimane Moulay Brahim (Engineering Proceedings, 2023)
The detection and diagnosis of power quality (PQ) issues are critical topics in the electrical power system’s generation, transmission, and distribution. Nonlinear loads, power electronic converters, system malfunctions, and switching events are the most common causes of PQ issues. The main purpose of this work is to use an artificial intelligence (AI) technique based on automatic feature extraction to discover and identify PQ difficulties. The AI technique consists of a dedicated architecture of the Long Short-Term Memory (LSTM) network, which is a special type of Recurrent Neural Network (RNN).